Kajian Literatur Terhadap Peran Transfer Pengetahuan Dalam Konteks Perusahaan Multinasional - Jondry Adrin Hetharie; Abraham Rieuwpassa (Univiversitas Dr. Djar Wattiheluw, 2022)
The purpose of this study is to demonstrate and summarize the important aspects of knowledge transfer in the context of multinational corporations. Design/methodology /approach; the review of aspects of SD is based on 15 journals published from 2005 to 2015 academic database, namely Emerald, by looking at the keywords